2019
DOI: 10.3390/clockssleep1030027
|View full text |Cite
|
Sign up to set email alerts
|

How Does Light Regulate Mood and Behavioral State?

Abstract: The idea that light affects mood and behavioral state is not new. However, not much is known about the particular mechanisms and circuits involved. To fully understand these, we need to know what properties of light are important for mediating changes in mood as well as what photoreceptors and pathways are responsible. Increasing evidence from both human and animal studies imply that a specialized class of retinal ganglion cells, intrinsically photosensitive retinal ganglion cells (ipRGCs), plays an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 94 publications
(118 reference statements)
0
7
0
3
Order By: Relevance
“…Non-visual effects of light comprise many physiological and neuropsychological measures in humans ranging from circadian gene expression to subjective perception of alertness and mood (for reviews, see 7,8 ). Another photoreceptor system besides rods and cones forms a key element in transmitting the non-visual action of light to the brain, namely the intrinsically photosensitive retinal ganglion cells (ipRGCs) containing the photopigment melanopsin.…”
Section: Introductionmentioning
confidence: 99%
“…Non-visual effects of light comprise many physiological and neuropsychological measures in humans ranging from circadian gene expression to subjective perception of alertness and mood (for reviews, see 7,8 ). Another photoreceptor system besides rods and cones forms a key element in transmitting the non-visual action of light to the brain, namely the intrinsically photosensitive retinal ganglion cells (ipRGCs) containing the photopigment melanopsin.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the bright blue lighting was the most arousing, and the green lighting with the low intensity was the least arousing. Milosavljevic 43 explored the light effects on mood and behaviour from a more scientific and medical perspective. Current understanding of the mechanisms and paths in which light information modulates behavioural state and mood are reviewed in this study.…”
Section: Effects Of Lightingmentioning
confidence: 99%
“…36 The improvement of the cognitive performance of the human brain under light exposure is reported in phototherapy of human mood disorders, including depressive discords and bipolar depression. 37,38 The development of the neuromorphic device helped us to investigate the effect of human emotions and mood swings on cognitive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Different neuroscience-related research has shown that human emotions (happy, mild, and sad) influence the cognitive process, including the attention, learning, and memory nature of the human brain. These cognitive activities are controlled by basic emotions, which have a direct impact on learning from environmental events . The improvement of the cognitive performance of the human brain under light exposure is reported in phototherapy of human mood disorders, including depressive discords and bipolar depression. , The development of the neuromorphic device helped us to investigate the effect of human emotions and mood swings on cognitive activity.…”
Section: Introductionmentioning
confidence: 99%